THE APPLICATION OF TAJWID LEARNING MODEL TO DEVELOP THE READING ABILITY OF AL-QUR'AN (Case study at the TPQ Barokah Gonilan, Kartasura, Sukoharjo 2019) - Rahmawati, Ririn Naila (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
Thih reasearch describe that TPQ Barokah is different from other common TPQ. In the TPQ Barokah using the system  where  it  combines  the  way  of the reading Qur’an using the method with pronunciation according to the correct  science rules.   The purpose of this research is to obtain information about the implementation  of the learning of the Qur'an in  the  application  of  science  tajwid  into  the  recitation  of  the  Qur'an  to develop the ability to read the Qur'an in the students of the TPQ Barokah Gonilan. The Methodology research. The results of this study showed that the study of the Qur'an in the TPQ Barokah Gonilan for the application of Tajwid science is different in accordance with the result of its class.  In the first  meeting the teacher more emphasis  on the understanding  of science material  tajwid  and  for  the  meeting  of  the  two  teachers  more  multiply reading practice of the Qur'an so that the ability to read the Qur'an students continues to evolve.